in vitro method for the analysis of infection-related morphogenesis in Fusarium graminearum - RITTENOUR, WILLIAM R; HARRIS, STEVEN D (Molecular plant pathology, 2010)
Fusarium graminearum is a significant pathogen of many cereal crops. With its genetic tractability, ease of culture, genome sequence availability and economic significance, F. graminearum has become the subject of intensive molecular research. Although molecular tools have been developed to enhance research into virulence determinants of F. graminearum, simple assays for infection-related development are lacking. As such, the objective of this study was to develop an in vitro protocol for the analysis of infection-related morphogenesis in F. graminearum. We demonstrate that two morphologically distinct hyphal structures are produced by F. graminearum during the invasion of detached wheat glumes: subcuticular hyphae and bulbous infection hyphae. Specialized wheat epidermal cells (papillae) appear to act as sites of invasion by F. graminearum on the adaxial side of detached wheat glumes. In addition, the development of bulbous infection hyphae is dependent on the pathogenicity mitogen-activated protein kinase Gpmk1, further supporting the infection-related nature of these structures. This relatively simple assay will contribute to the tractability of the F. graminearum system and help to uncover molecular requirements for infection-related development.